2017
DOI: 10.1016/j.preteyeres.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Detection and measurement of clinically meaningful visual field progression in clinical trials for glaucoma

Abstract: Glaucomatous visual field progression has both personal and societal costs and therefore has a serious impact on quality of life. At the present time, intraocular pressure (IOP) is considered to be the most important modifiable risk factor for glaucoma onset and progression. Reduction of IOP has been repeatedly demonstrated to be an effective intervention across the spectrum of glaucoma, regardless of subtype or disease stage. In the setting of approval of IOP-lowering therapies, it is expected that effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
129
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 127 publications
(200 reference statements)
2
129
0
12
Order By: Relevance
“…De Moraes et al proposed that decreasing the rate of visual field progression by 30% in a clinical trial of 12 to 18-month duration would yield clinically meaningful results and showed that a 30% decrease in rate of visual field progression had a significant effect on health-related quality of life. 76 It has also been suggested that the 10-2 visual field may be a more appropriate outcome measure as the 24-2 field can underestimate the degree of damage at the macular region involved in glaucomatous optic neuropathy. 77 The 10-2 visual field has also been shown to correlate with quality of life outcome measures 78 and may reduce the time required to detect glaucomatous progression.…”
Section: Optimising Clinical Trial Endpointsmentioning
confidence: 99%
“…De Moraes et al proposed that decreasing the rate of visual field progression by 30% in a clinical trial of 12 to 18-month duration would yield clinically meaningful results and showed that a 30% decrease in rate of visual field progression had a significant effect on health-related quality of life. 76 It has also been suggested that the 10-2 visual field may be a more appropriate outcome measure as the 24-2 field can underestimate the degree of damage at the macular region involved in glaucomatous optic neuropathy. 77 The 10-2 visual field has also been shown to correlate with quality of life outcome measures 78 and may reduce the time required to detect glaucomatous progression.…”
Section: Optimising Clinical Trial Endpointsmentioning
confidence: 99%
“…This situation makes that, all current pharmacological and surgical treatments aim to reduce IOP [19] [20] [21]. However, although this approach is effective for many patients with glaucoma, a significant proportion of their visual function deteriorates inexorably.…”
Section: Introductionmentioning
confidence: 99%
“…However, although this approach is effective for many patients with glaucoma, a significant proportion of their visual function deteriorates inexorably. In fact, about one in eight patients with glaucoma become blind in at least one eye despite this treatment [6] [21]. In animals, experimental therapies targeting and protecting retinal ganglion cells against phenomena related to hypoperfusion of the optic nerve (ischemia, hypoxia, oxidative stress, apoptosis) have been evoked and grouped under the term neuroprotection [6] [22]- [27].…”
Section: Introductionmentioning
confidence: 99%
“…The pathobiology of this neurodegenerative disease remains unclear due to manifold processes and risk factors, including age, ethnic group and elevated intraocular pressure (IOP) 2 . Current therapies can successfully lower IOP and decelerate but not halt the progression of neurodegeneration 3 . Thus, developing neuroprotective approaches to interrupt progression is a primary goal 4 .…”
Section: Introductionmentioning
confidence: 99%